Sandwich cryogenic pipeline - Albarody, T.M.B. (Offshore Technology Conference, 2014)
As the development of offshore gas reserves is growing rapidly, the LNG elements have to adapt always to new needs. In this paper, LNG transfer system proposed to operate at platform areas and to accommodate with subsea conditions. Such cryogenic pipe offers an opportunity to have rigid pipeline could lain on seabed offering a cheaper solution than complex trestles. As pipe-in-pipe system, whose main body is a cryogenic sandwich pipe concentrated inside a carrier pipe. The sandwich pipe assembly contains two layers made of several grades of stainless steel such as: Type 316 stainless steel (ASTM A312), 9 Ni-Iron alloy (ASTM 333), and/or, Invar (36 Nickel-Iron alloy), and reinforced with helical armor wires to sustain the hoop load. The design philosophy is inspired by both traditional pipeline and the international gas codes, tending to eliminate the improbable and catastrophic failures. The carrier pipe could made of common carbon steel with conventional corrosion protection, acting as armor for internal parts, preventing water ingression, and gives an adequate strength at laying operation. However, the major concern of this study is on the inner pipe only. Copyright 2014, Offshore Technology Conference.